Multiple teaching methods in undergraduate surgical training: a blended style may be the optimal choice! - Zhu, Lingling; Zhang, Qin; Zhang, Yang (Frontiers in Education, 2023)
Background: There are various methods for teaching surgery to undergraduate students. Lecture-based learning (LBL) is a teacher-centered approach that comprehensively, accurately, and systematically conveys knowledge. Team-based, case-based, and problem-based learning methods are student-centered approaches that increase student enthusiasm and subject-related motivation. However, the COVID-19 pandemic disrupted conventional methods for teaching surgery to undergraduate students and its impact continues even today. This research investigates a variety of surgical teaching strategies and suggests optimal strategies for undergraduate students, especially within the context of the COVID-19 crisis. Methods: Various teaching methods in undergraduate medical education that have emerged over the last five years are reviewed and analyzed, specifically those used for surgical training during the COVID-19 pandemic. Results: Traditional in-person teaching methods have been replaced by novel approaches that increase efficiency, including social media adoption, simulation-based training, flipped-classroom concepts, and “Hand as Foot” teaching. However, traditional and novel approaches can be combined to teach students the fundamentals of science and basic surgical skills, which include incision, suturing and drainage, and chest tube insertion. Each method has its advantages and disadvantages under certain circumstances. Conclusion: Several alternative teaching strategies and a combination of methods can complement traditional face-to-face learning, promoting the successful dissemination of academic knowledge and the improvement of clinical surgical skills in terms of objectivity, time-efficiency, and feasibility. The effects of the COVID-19 pandemic on the learning context can provide a reference for future teaching in response to unavoidable emergencies.